2020
DOI: 10.3389/fpsyg.2019.02976
|View full text |Cite
|
Sign up to set email alerts
|

Can Academic Achievement in Primary School Students Be Improved Through Teacher Training on Emotional Intelligence as a Key Academic Competency?

Abstract: Background: The primary aim of the current study was to develop a multimethodological teacher training program based on emotional intelligence (EI) as a key competency in order to improve student academic achievement based on two methods: face-to-face instruction and game-based e-learning instruction. Methods: Seventy-four primary education teachers and their 2069 students were randomly assigned to three groups. The first group of teachers (n = 23) were trained to use a face-to-face method. The objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 27 publications
3
36
0
4
Order By: Relevance
“…Lurea et al (2011) has concluded that a good teaching method and style is reflected in the embodiment of training values and enhance their understanding and motivates students to think critically and believe in themselves. Rico and Sandoval (2020) supports this claim based on their findings which shows that implementation of emotional intelligence into classroom teaching effectively improve the academic achievement of primary school learners; however, they found a greater increase in academic achievement and higher teacher satisfaction in the game-based e-learning group. They concluded that emotional intelligence is the key towards academic competency.…”
Section: Academic Performance Of Pupilsmentioning
confidence: 52%
See 1 more Smart Citation
“…Lurea et al (2011) has concluded that a good teaching method and style is reflected in the embodiment of training values and enhance their understanding and motivates students to think critically and believe in themselves. Rico and Sandoval (2020) supports this claim based on their findings which shows that implementation of emotional intelligence into classroom teaching effectively improve the academic achievement of primary school learners; however, they found a greater increase in academic achievement and higher teacher satisfaction in the game-based e-learning group. They concluded that emotional intelligence is the key towards academic competency.…”
Section: Academic Performance Of Pupilsmentioning
confidence: 52%
“…The researcher believed that emotional intelligence is highly important for quality education. While the hypothesized finding of Rico and Sandoval (2020) on the emotional intelligence of teachers and the academic achievement of the learners claimed that there is no significant difference observed in the learner's achievement from the control group.…”
Section: Figure 1 Academic Performance Of Pupils In Tampilisan Districtmentioning
confidence: 95%
“…En cuanto a cómo se está trabajando formalmente la IE, es preciso destacar algunas respuestas: en asambleas o por medio del teatro, ya que son coincidentes con alguna de la bibliografía utilizada en este trabajo (Gómez Vicario et al, 2017;Morán Iranzo et al, 2016). Sin embargo, las personas encuestadas no hacen alusión expresa a la gamificación o al aprendizaje cooperativo, las cuales son opciones sobre las que existen diferentes referencias contextualizadas en primaria (Pozo-Rico y Sandoval, 2020;Rivera-Pérez et al, 2021). No obstante, si se tienen en cuenta los resultados vinculados al código libre materiales, se aprecia cómo el juego sí es un recurso utilizado por diferentes docentes; al igual que los cuentos, los cuales también son un óptimo recurso para trabajar las emociones desde las primeras edades (Cerezo Ros, 2021).…”
Section: Discussionunclassified
“…In recent decades, there has been a rise in the evidences found on the importance of scholar school violence prevention (Gazquez et al, 2007;Loan et al, 2018;Modin et al, 2018; Nation et al, 2020;Xu et al, 2020), the relevance of training Youngsters' Social Skills (Donohue, 2005;Matson et al, 2007;Wang et al, 2011;Youngstrom et al, 2017) and the convenience of instruction for EI competency among the students of primary school (Petrides et al, 2006(Petrides et al, , 2016Nelis et al, 2009Nelis et al, , 2011Durlak et al, 2011). However, while the evidence for the importance of these variables has been highly studied, more front-line applied researches are needed to improve these factors' (prevention of school violence and promotion of socio-emotional skills) importance in the school context in the early academic years (Pozo-Rico and Sandoval, 2020). In the light of the results obtained, the program proposed in this research has been useful for the prevention of violent behaviors in the educational field, promoting the development of social and emotional skills among the students enrolled in the 3rd year of primary education.…”
Section: Discussionmentioning
confidence: 99%